Pragmatism and hermeneutics: Rorty, James and Gadamer on truth. - Pollock, Albert. (University of Ottawa (Canada), 1996)
Inspired by Richard Rorty's attempt to exploit both pragmatism and philosophical hermeneutics in support of his own end of epistemology project, the dissertation presents a comparative study of William James' pragmatic theory of truth and Hans-Georg Gadamer's philosophical hermeneutic account of human understanding. Chapter 1 examines Rorty's end of philosophy project and his critique of truth as correspondence. It identifies three fundamental orientations of his thought, namely, the rejection of: representationalism, the ideal of transcendence, and scientism. It examines his claim that the pragmatic theory of truth and philosophical hermeneutic account of understanding are best understood as thorough repudiations of the representational intuition and the ambition for transcendence that inform the traditional meaning of philosophy and truth. It identifies the two aims of the thesis: first, to compare William James' pragmatic theory of truth and Hans-Georg Gadamer's account of human understanding, and second, to critically reflect on Rorty's general deconstruction of truth in light of the findings. Chapter 2 presents a straightforward interpretation of William James' pragmatic theory of truth bearing Rorty's three orientations in mind. It employs three questions as interpretive guides: How does James' concept of truth stand in relation to the representational intuition? How does it stand in relation to the ideal of transcendence? How does it challenge scientism? Chapter 3 compares Gadamer's philosophical hermeneutic account of understanding to James' theory of truth. It demonstrates their agreement concerning the primordial, interpretive structure of thought and the temporal, situated nature of truth. This chapter reveals that Gadamer, like James, wants to correct false thinking about science and truth. Both reject scientism. Consequently, they propose a more primordial and universal account of human understanding and truth than is circumscribed by science and scientific method per se. Both understand the breach between scientific consciousness and aesthetic, moral and religious consciousness to be the central problem of modern thought. Chapter 4 presents a critical reflection on Rorty's general deflation of truth in light of the comparative reading of James and Gadamer. It argues that Rorty remains entrapped by Cartesian metaphysical doubt and the identification of truth with certainty and that this leads to the extremity of his incoherent repudiation of the traditional notion of truth informed by the representational intuition and the ambition for transcendence. This chapter attempts to make clear how non-negotiable are the ambition for transcendence and the representationalist intuition, in contributing to the coherency of theoretical inquiry as such. It also argues that the essence of the liberal ironist society that Rorty promotes is entirely dependent upon the conception of inquiry that he denies. (Abstract shortened by UMI.)
Keywords: Philosophy.